Analisis penerapan sistem dan prosedur akuntansi dalam pengelolaan dana desa tahun 2023 di Desa Kanonang Satu - Gobel, Novita Srikandi Gloria; Sabijono , Harijanto; Tirayoh , Victorina Z. (Riset Akuntansi dan Portofolio Investasi, 2024)
This research was conducted with the aim of knowing how accounting systems and procedures are applied at the Kanonang Satu Village Office. This research is qualitative research using a descriptive approach. The data collection techniques used were observation, interviews, and documentation. The results showed that accounting systems and procedures in financial management in Kanonang Satu Village were in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. It is just that at the accountability reporting stage the village government does not inform the community every 6 months properly and the old accountability report legally only delegates tasks to village operators so that the village fund reporting procedure in Kanonang Satu village is less effective.